Thunder dog : the true story of a blind man, his guide dog, and the triumph of trust at Ground Zero - Hingson, Michael, 1950-; Flory, Susy, 1965- (Nashville, Tenn. : Thomas Nelson, 2011)
Discover how blindness and a bond between dog and man saved lives and brought hope during one of America's darkest days
Includes bibliographical references (p. 229-230).
Keywords: Hingson, Michael, -- 1950-; September 11 Terrorist Attacks, 2001 -- Personal narratives; Blind -- United States -- Biography; Human-animal relationships